Isocyanate asthma: respiratory symptoms due to 1, 5-naphthylene di-isocyanate. Issue 6 (December 1979) - Harries, M G; Burge, P S; Samson, M; Taylor, A J; Pepys, J
Abstract : Occupationally related asthma developing in three patients due specifically to exposure to 1, 5-naphthylene di-isocyanate (NDI), a hot curing agent used in manufacturing rubber, has been confirmed for the first time using bronchial provocation testing. This substance has been thought to be safer than toluene di-isocyanate (TDI) and diphenylmethane di-isocyanate (MDI) because of its relatively high melting point (120 degrees C). Each patient worked in the same factory and the circumstances of exposure were similar. Provocation testing was also performed with TDI in concentrations up to 0.018 parts per million (ppm) and MDI in concentrations up to 0.02 ppm, to which the patients had been exposed in the past, but no reactions were elicited. None of the patients had increased bronchial reactivity judged by histamine lability and exercise testing. Each patient was advised to give up his job, but two of the three could not find alternative employment and remained exposed. Three-year follow-up shows that airways narrowing has persisted in those who have remained exposed.